Ordinance No. 79: An Ordinance Relating to Crimes and Punishments, in Scandia Journal, Jan. 5, 1894, at 8, § 6 - (:unkn) unknown (My University, 1894)
§ 6: Every person who shall, within the corporate limits of the city of Scandia, carry or have upon their person any concealed pistol, revolver, bowie-knife, dirk, sling-shot, billy, knuckles or other deadly weapon, shall upon conviction be fined in any sum not less than Two ($2.00) Dollars, nor more than Fifty ($50.00) Dollars. Provided:-That any person engaged in a lawful occupation and of good moral character, may, by the mayor, be granted a permit to carry such concealed weapons.
Keywords: CARRY